2010
DOI: 10.1002/hed.21381
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyr61 (CCN1) in human oral squamous cell carcinoma: An independent marker for poor prognosis

Abstract: Cyr61 is a positive growth modulator of oral SCC and Cyr61 overexpression is an independent prognostic indicator for patients with oral SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
(46 reference statements)
1
23
0
1
Order By: Relevance
“…Several of these 11 genes have already been associated with cancer progression. For example, Cyr61 has been associated with poor prognosis in squamous cell cancers of the head and neck (25) and esophagus (26). CCR2 has been linked to breast cancer metastasis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Several of these 11 genes have already been associated with cancer progression. For example, Cyr61 has been associated with poor prognosis in squamous cell cancers of the head and neck (25) and esophagus (26). CCR2 has been linked to breast cancer metastasis (27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to angiogenesis, CCN1 can also promote cancer cell proliferation, invasion, survival, and metastasis [74,75,141]. Accordingly, subsequent studies have shown that forced expression of CCN1 enhanced tumor growth in xenografts of breast cancer cells [142], prostate cancer cells [74], ovarian carcinoma cells [78], and squamous carcinoma cells [143]. Consistently, silencing of CCN1 expression decreased tumor growth in xenografts of prostate cancer cells [74] and pancreatic cancer cells [144].…”
Section: Ccn1 In Pathologiesmentioning
confidence: 99%
“…The clinical relevance of these observations is supported by the finding of a significant correlation between CCN1 expression and the stage, tumor size, lymph node positivity, and poor prognosis in several cancers, including breast cancer [142,145–148], prostate cancer [149], glioma [150], gastric adenocarcinoma [151], and squamous cell carcinoma [143]. In MCF7 breast cancer cells, which are dependent on estrogen for growth, overexpression of CCN1 renders these cells estrogen-independent and significantly resistant to apoptosis, in part through upregulation of the anti-apoptotic protein XIAP [81,152,153].…”
Section: Ccn1 In Pathologiesmentioning
confidence: 99%
“…In fact, the increased presence of one or multiple members of the CCN family is associated with poor prognosis in breast, prostate, pancreatic, renal, bone, head and neck, and brain cancers (186190). More specifically, CCN4 is upregulated in early stages of prostate cancer and correlated with higher circulating levels of the protein (191).…”
Section: Introductionmentioning
confidence: 99%